Complete response in a patient with gynecological hidradenocarcinoma treated with exclusive external beam radiotherapy and brachytherapy: a case report - Giannelli, Flavio; Chiola, Ilaria; Belgioia, Liliana; Garelli, Stefania; Pastorino, Alice; Marcenaro, Michela; Mammoliti, Serafina; Costantini, Sergio; Bizzarri, Nicolò; Vellone, Valerio; Barra, Salvina; Corvò, Renzo (Journal of Contemporary Brachytherapy, 2017)
Hidradenocarcinoma (HC) is a very rare disease. This case report illustrates a successful treatment of a 60-year-old woman with vulvo-vaginal localization of hidradenocarcinoma treated with external beam radiotherapy delivered by helical tomotherapy with a simultaneous integrated boost (SIB), followed by brachytherapy. External beam radiotherapy dose prescription was 50.4 Gy in 28 fractions, five fractions per week to whole pelvis (planning target volume 1 – PTV1), 60.2 Gy in 28 fractions to SIB1 (fundus of uterus and right inguinal node), and 58.8 Gy in 28 fractions to SIB2 (lower/middle third of vagina, paraurethral region and right inguinal lymph nodes). Brachytherapy dose prescription was 28 Gy in 4 fractions for cervix, fundus of uterus and upper third of vagina (HR-CTV1), and 22 Gy in 4 fractions to middle third of vagina and paraurethral region (HR-CTV2). D90 for whole treatment was 91.9 Gy and 86.0 Gy for HR-CTV1 and HR-CTV2, respectively. Patient remained 12-months disease-free without treatment related side effects.